Multimodal communicative acts of Thailand’s private hospital website promoting medical tourism - Wan Fatimah Solihah Wan Abdul Halim,; Intan Safinaz Zainudin,; Nor Fariza Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Websites of private hospitals are significant channels for delivering the communicative acts in relation to information of hospitals’ facilities and expertise to international medical tourists. However, studies that involved communicative acts have mainly focused on examining the language mode. It overlooked the multimodal perspective which hinder prospective international medical tourists from receiving the intended promotional messages. This study, therefore, aims to examine multimodal realisations of representative and commissive communicative acts in Thailand’s private hospital website. Within Systemic Functional Linguistic (SFL) perspective, Halliday & Matthiessen’s model of textual analysis (2004) and Daneš’ classification of thematic patterns (1974) were utilised for language analysis, while Kress and van Leeuwen’s (2006) framework was adopted for visual analysis. Three webpages from a Thai private hospital website were analysed in relation to theme types and thematic progression for textual function in language analysis, and information value, saliency and framing elements for compositional function in visual analysis. Results based on the analysis of the communicative acts in the selected webpages aimed to inform and persuade prospective medical tourists. The multimodal communicative acts created a technologically established, sophisticated, reliable and caring representation of Samitivej Hospital through the high occurrence of unmarked themes, reiteration patterns, salient visuals and absence of framing. The findings provided communicative strategies to promote medical tourism to copywriters, website designers and medical tourism stakeholders in designing such websites.